Consolidation with high-dose chemotherapy and stem cell support for responding patients with metastatic soft tissue sarcomas: prospective, single-institutional phase II study - Kasper, Bernd; Scharrenbroich, Peter-Ingo; Schmitt, Thomas; Wuchter, Patrick; Dietrich, Sascha; Ho, Anthony Dick; Egerer, Gerlinde (Bone marrow transplantation, 2009)
Prognosis of patients with metastatic soft tissue sarcoma remains poor. Whether high-dose chemotherapy with stem cell support improves the long-term outcome for these patients is debatable. We present a prospective, single-institutional phase II study that enrolled 34 soft tissue sarcoma patients with advanced and/or metastatic disease. After four courses of chemotherapy consisting of doxorubicin and ifosfamide, responding patients in at least partial response (PR) were treated with high-dose chemotherapy (n=9); all other patients continued chemotherapy for two more cycles. After standard chemotherapy, PR (n=10), stable disease (SD, n=6) and progressive disease (PD, n=14) were attained for the evaluable patients. Twenty-nine patients died and five are alive with the disease. Median PFS was 11.6 months (range 8-15) for patients treated with high-dose chemotherapy (n=9) vs 5.6 months (range 0-19) for patients treated with standard chemotherapy. Median OS was 23.7 months (range 12-34) vs 10.8 months (range 0-39), respectively. The subgroup of patients treated with high-dose chemotherapy gained significant survival benefit. Nevertheless, high-dose chemotherapy as a possible consolidation strategy remains highly investigational.